Revisiting New Public Management and Public Service Performance: A Leadership Behavior Perspective - Herman Herman; Shofia Amin; Sigit Indrawijaya; Sry Rosita (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to revisit the relationship between New Public Management (NPM) and public service performance by examining leadership behavior as a mediating mechanism within the Jambi Provincial Government. Research Methodology: This study used a quantitative explanatory design in the context of the Jambi Provincial Government, Indonesia. Data were collected from 126 civil servants across seven regional agencies through stratified random sampling and analyzed using SEM-PLS with SmartPLS 4.0. Results: The findings show that New Public Management significantly influences task-, change-, and relationship-oriented leadership behaviors and directly improves public-service performance. However, leadership behavior neither significantly affected service performance nor mediated the relationship between NPM and service performance. Conclusions: These findings suggest that managerial reforms associated with NPM contribute directly to improvements in public service performance while simultaneously shaping leadership behavior in public organizations. Nevertheless, leadership behavior does not function as a statistically significant mediating mechanism in the relationship between NPM and the service performance. Limitations: This study is limited to civil servants in selected regional government agencies in Jambi Province and relies on perception-based survey data, which may reduce generalizability and introduce subjective bias. Contributions: This study contributes to the NPM and public leadership literature by clarifying that leadership behavior does not necessarily function as a mediating mechanism in the relationship between NPM and public service performance in local government contexts.